Financial friction, resource misallocation and total factor productivity: Theory and evidence from China - Yanli Wang; Xiaodong Lei; Fan Yang; Na Zhao (Journal of Applied Economics, 2021)
We explore the impact of financial friction on resource misallocation and total factor productivity (TFP) of China. First, the mathematical models are derived to clarify the mechanism and consequence of resource misallocation, showing that financial friction leads to resource mismatch, and thus results in the loss of TFP. Second, taking the dataset of China as the research sample, we establish econometric models to explore the impacts of financial friction on resource allocation and TFP. The results show that financial friction has negative impact on the TFP of China. In addition, the friction of financial markets will lead to factor distortion. Furthermore, the results of mechanism analysis demonstrate that resource misallocation is an important channel through which financial friction deteriorates the TFP of China, which is verified at the enterprise and province levels, respectively.
Keywords: 330; China; Financial friction; resource misallocation; total factor productivity (TFP)